Mitochondrial Activity of the Locally Established Rat Embryo Fibroblast Cell Line Through Different Passages - kadhim, Husam Al-Deen M . (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Mitochondria are the cell’s powerhouse, the site where the vast majority of ATP is synthesized. Mitochondrial activity represent a central checkpoint for detection of the difference between cancer cells and normal cells at the metabolic profile.Objective: To find out if there is a correlation between in vitro transformation and mitochondrial activity, by measuring the activity during clonal evolution of the locally established rat embryo fibroblast (REF) cell line throughout studying different passages.Materials & Methods: The (REF) cell line, was in vitro cultured. Mitochondria were isolated by differential centrifugation following Mitochondria Isolation Kit. Enzymatic activity of intact mitochondria has been measured using Cytochrome C Oxidase Activity Assay Kit. The decrease in absorbance at 550nm as horse heart ferrocytochrome c was oxidized has been monitored.Results: Depending on the conducted colorimetric assay, cytochrome c oxidase activity was measured, for the three different passages (42, 72 and 91) of REF cell line. At 550 nm, spectral data were valued (0.247, 0.723 and 1.318) unit/ml for three passages of REF cells (42, 72 and 91) respectively.Conclusion: There was a significant relationship between the mitochondrial activity and the age (passage number) for these in vitro cultured cells. These variations probably due to the transformational events that have been occurred during long-term continuous subculture